2016
DOI: 10.1007/s00253-016-7655-9
|View full text |Cite|
|
Sign up to set email alerts
|

Novel nitrifiers and comammox in a full-scale hybrid biofilm and activated sludge reactor revealed by metagenomic approach

Abstract: Biofilms are widely used in wastewater treatment for their particular enhancement of nitrogen removal and other significant advantages. In this study, the diversity and potential functions of nitrogen removal bacteria in suspended activated sludge (AS) and biofilm of a full-scale hybrid reactor were uncovered by metagenomes (∼34 Gb), coupled with PCR-based 454 reads (>33 K reads). The results indicated that the diversity and abundance of nitrifiers and denitrifiers in biofilm did not surpass that in AS, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 55 publications
(70 reference statements)
8
48
1
Order By: Relevance
“…Furthermore, it is possible that the Nitrospira co-occurring with Candidatus Brocadia were Nitrospira species with the genetic potential for comammox, as a fluorescence in-situ hybridization study confirmed the extensive aggregation of the 2 phylotypes in hypoxic conditions (<3.1 µM O 2 ) (Van Kessel et al, 2015). Despite Nitrospira comammox being identified in numerous aquatic environments (Chao et al, 2016; Daims et al, 2015; Pinto et al, 2016), we cannot conclusively identify comammox without sequencing the ammonia monooxygenase gene (Pinto et al, 2016; Van Kessel et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is possible that the Nitrospira co-occurring with Candidatus Brocadia were Nitrospira species with the genetic potential for comammox, as a fluorescence in-situ hybridization study confirmed the extensive aggregation of the 2 phylotypes in hypoxic conditions (<3.1 µM O 2 ) (Van Kessel et al, 2015). Despite Nitrospira comammox being identified in numerous aquatic environments (Chao et al, 2016; Daims et al, 2015; Pinto et al, 2016), we cannot conclusively identify comammox without sequencing the ammonia monooxygenase gene (Pinto et al, 2016; Van Kessel et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…NirK, the gene for Cu-NIR, is also present in comammox, but no evidence of NO accumulation in comammox enrichments cultures suggests that nitrite reduction may not be particularly robust (Daims et al, 2015). Comammox have been found in different water engineered systems, including WWTPs (Chao et al, 2016;Gonzalez-Martinez et al, 2016;Pjevac et al, 2017). However, their abundance in wastewater treatment plants is lower than AOB, which is likely due to the competitive advantage of AOB in systems with high substrate concentrations (Costa et al, 2006;Kits et al, 2017).…”
Section: Complete Ammonia Oxidizing Bacteriamentioning
confidence: 99%
“…In the latter case, Chao et al (2016) [3], have emphasized that the biofi lm in aerobic reactors is exposed to the dissolved oxygen (DO) concentration gradient, which may induce the growth of comammox bacteria. Earlier cross-section studies of biomass distribution in nitrifying biofi lm systems (Okabe et al 1999) found the highest NOB abundance in deeper zones with less DO availability.…”
Section: Discovery Of Comammoxmentioning
confidence: 99%
“…All comammox organisms identifi ed to date belong to "Candidatus Nitrospira nitrosa", "Candidatus Nitrospira nitrifi cans", "Candidatus Nitrospira inopinata", and Nitrospira sp. strain Ga0074138 [2,13] [3,13]. However, the metagenomics analysis does not provide information about the activity of those bacteria.…”
Section: Microbiology Of Comammoxmentioning
confidence: 99%
See 1 more Smart Citation